Perfection Enterprise / Muhammad Yurid Hamdan Nasir … [et al.] - Hamdan Nasir, Muhammad Yurid Hamdan Nasir; Hamdan, Nazwatul Hazirah; Hasnol, Nurul Nabila; Jaafar, Siti Nazira; Mohd Khir, Siti Nurdiana (2022)
MISSION Perfection creates the best printing service (Printfection) company with high technology to help the education and economy achieve their motive. VISION To assist and relieve people's burdens, and to become Malaysia's most well-known and trusted provider of print and marketing solutions. INTRODUCTION This company has small and medium-sized enterprises (SMEs) employing fewer than 250 people. Perfection Enterprise right now only has 10 people working in the company. The size of capital is estimated at LOCATION Perfection Enterprise presently operates from one large office located in Shah Alam, Selangor. All manufacturing is out-sourced to contract manufacturers. MANAGEMENT The Management of Perfection Enterprise led by owner/founder which is Muhammad Yurid. 1. Organisational Structure - Our Company is a divisional structure as we divide into several departments, such as Human Resources Management, Finance Management, Sales & Marketing management and Product Management 2. Divisions of a firm have authority over their own resources, allowing them to function almost independently within the broader organisation. 3. Management teams - Our teams lead by owner Muhammad Yurid, and the rest management is Nazwatul Hazirah Binti Hamdan as Human Resource Manager, Siti Nazira Binti Jaafar as Finance Manager, Siti Nurdiana Binti Mohd Khir as Marketing and Sales Manager and Nurul Nabila Binti Hasnol as Production Manager.